Association of EGF, IGFBP-3 and TP53 gene polymorphisms with major depressive disorder in Slovak population - Evinova, Andrea; Evinová, Andrea; Škereňová, Mária; Ondrejka, Igor; Lehotský, Ján (Central European Journal of Public Health, 2016)
BACKGROUND: Major depressive disorder (MDD) is a main public health concern worldwide. Despite extensive investigations, the exact mechanisms responsible for MDD have not been identified. Epidermal growth factor (EGF) and insulin growth factor binding protein-3 (IGFBP-3) are involved in brain function. Tumour suppressor protein p53 is widely involved in neuronal death in response to different forms of acute insults and neurological disorders. The present study focuses on the possible associations of the single-nucleotide polymorphisms (SNP) of EGF A61G (rs4444903), IGFBP-3 C32G (rs2854746) and TP53 G72C (rs1042522) genes with MDD risk in the Slovak population. METHODS: The present case-control association study was carried out in 111 confirmed MDD patients and 207 healthy subjects. Genotyping was performed by polymerase chain reaction-restriction fragment length polymorphism methods. RESULTS: Logistic regression analysis showed no association between SNPs of selected genes and MDD risk in the Slovak population. However, the stratification of individuals by gender revealed that males carrying IGFBP-3 G alleles (G32G or GG) had marginally increased risk for developing MDD as compared to CC homozygous males (p=0.09). In women, inverse association was observed between SNP rs1042522 and MDD risk (p=0.04 for recessive model). CONCLUSION: Our results suggest the protective effect of minor allele 72C of TP53 gene towards MDD. The disruption of mechanisms involved in cell survival and death regulation may be involved in pathophysiology of MDD.
Keywords: dospělí; Genotype; Depressive Disorder, Major; Female; IGFBP-3; Genes, p53; polymerázová řetězová reakce; polymorfismus délky restrikčních fragmentů; Adult; Polymerase Chain Reaction; ženské pohlaví; jednonukleotidový polymorfismus; Slovakia; geny p53; lidé; depresivní porucha unipolární; Polymorphism, Single Nucleotide; genotyp; genetická predispozice k nemoci; studie případů a kontrol; Aged, 80 and over; Genetic Predisposition to Disease; epidermální růstový faktor; Polymorphism, Restriction Fragment Length; Insulin-Like Growth Factor Binding Protein 3; Male; Case-Control Studies; Aged; alely; Alleles; lidé středního věku; senioři nad 80 let; Slovenská republika; senioři; mužské pohlaví; Epidermal Growth Factor; Middle Aged; Humans